Clinical Guidelines and Management of Ankyloglossia with 1-Year Followup: Report of 3 Cases - Mayur S. Bhattad; M. S. Baliga; Ritika Kriplani (Case Reports in Dentistry)
The tongue is an important oral structure that affects speech, position of teeth, periodontal tissue, nutrition, swallowing, nursing, and certain social activities. Ankyloglossia (tongue tie) is a congenital anomaly characterized by an abnormally short, thick lingual frenulum which affects movement of tongue. Though the effect of ankyloglossia in general appears to be a minor condition, but a major difference exists concerning the guidelines for tongue-tie division. There are no accepted practical criteria for the management of such condition, and hence this paper aims at bringing all the compilation in examination, diagnosis, treatment, and management of tongue tie together for better clinical approach.